The Importance of Instructional Leadership in Schools - Rosyada, Sri Rahayu Amrina; Citriadin, Yudin; Harmansyah, Harmansyah (Pascasarjana Universitas Mataram, 2025)
Learning leadership is very important because it contributes greatly significant impact on increasing student learning achievement, ble to provide encouragement towards the school community to improve student learning achievement, focus the activities of its citizens toward achieving the school’s vision, mission goals, building a learning community for its citizens and even being able to create a school as a learning school. Ironically, only 16% of the 856 school principals wre found carry out the role of learning ledership. Instructional leadership is strategically used to improve the quality of learning. This leadership style is leadership oriented to improve the quality of learning, instructional leadership policy becomes the parameters of the school in improving the quality of leaners’ learning outcomes. It can be concluded that instructional leadership is effective in improving the quality of learning